Exosome-encapsulated ncRNAs: Emerging yin and yang of tumor hallmarks - Khan, Nazoora; Umar, Mohd Saad; Haq, Mohamed; Rauf, Talha; Zubair, Swaleha; Owais, Mohammad (Frontiers in Genetics, 2022)
Tumorigenesis is a multifaceted process, where multiple physiological traits serving as cancer’s distinctive characteristics are acquired. “Hallmarks of cancer” is a set of cognitive abilities acquired by human cells that are pivotal to their tumor-forming potential. With limited or no protein-coding ability, non-coding RNAs (ncRNAs) interact with their target molecules and yield significant regulatory effects on several cell cycle processes. They play a “yin” and “yang” role, thereby functioning both as oncogenic and tumor suppressor and considered important in the management of various types of cancer entities. ncRNAs serve as important post-transcriptional and translational regulators of not only unrestricted expansion and metastasis of tumor cells but also of various biological processes, such as genomic mutation, DNA damage, immune escape, and metabolic disorder. Dynamical attributes such as increased proliferative signaling, migration, invasion, and epithelial–mesenchymal transition are considered to be significant determinants of tumor malignancy, metastatic dissemination, and therapeutic resistance. Furthermore, these biological attributes engage tumor cells with immune cells within the tumor microenvironment to promote tumor formation. We elaborate the interaction of ncRNAs with various factors in order to regulate cancer intra/intercellular signaling in a specific tumor microenvironment, which facilitates the cancer cells in acquiring malignant hallmarks. Exosomes represent a means of intercellular communication and participate in the maintenance of the tumor hallmarks, adding depth to the intricate, multifactorial character of malignant neoplasia. To summarize, ncRNAs have a profound impact on tumors, affecting their microcirculation, invasiveness, altered metabolism, microenvironment, and the capacity to modify the host immunological environment. Though the significance of ncRNAs in crosstalk between the tumor and its microenvironment is being extensively explored, we intend to review the hallmarks in the light of exosome-derived non-coding RNAs and their impact on the tumor microenvironment.